Characterization and Development of Fluidizing Velocity Profile of Sand Particles in Fluidized Bed Combustor (FBC) - Ahmmad Shukrie, Md Yudin; Shahrani, Anuar; Azri, Alias (2014)
When gas is passed through an inert bed of solid particles such as sand, supported on a perforated plate, the gas, initially, will seek a path of least resistance and pass upward through the sand. With further increased in the gas velocity, the gas starts bubbling through the bed and the particles attain the state of high turbulence. Under such conditions, the bed assumes the appearance of a fluid and exhibits the properties associated with a fluid and hence it is called 'fluidized Bed'. If the velocity is too low,fluidization will not occur, and if the gas velocity becomes too high, the particles will be entrained the gas stream and lost. Hence, to sustain stable operation of the bed, it must be ensured that the gas velocity is maintained between minimum fluidization velocity and particle entrainment velocity.